Home Pharmacy Care Penyakit Tidak Menular di Samarinda - Indriyanti, Niken; Samsul, Erwin; Siregar, Vita Olivia; Rezekilah, Rezekilah; Kawareng, Andi Tenri; Faisal, Muhammad; Suparningtyas, Juniza Firdha (Universitas Pahlawan Tuanku Tambusai, 2023)
Home pharmacy care on non-contagious patients is necessary to increase the quality of therapeutic outcome. This program was done in a district in Samarinda. Participant selection was done by participating of nearest primary health facility. Permissions were given from the district and the nearest health facility. Three visitations were done for determination, education, and evaluation steps. The personal education during this program shows a positive impact on the own responsibility of self adherence under drug regimen. Generally, medical examination on blood pressure, blood glucose, and others are better after effective education of this program. Education output of this program is useful to increase patient’s adherence to drug regimen and healthy lifestyle.